2018
DOI: 10.15255/kui.2017.028
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous PtSnO2/C Catalyst with Enhanced Catalytic Activity for Ethanol Electro-oxidation

Abstract: In this paper, we report the synthesis, characterization, and electrochemical evaluation of a mesoporous PtSnO 2 /C catalyst, called PtSnO 2 (M)/C, with a nominal Pt : Sn ratio of 3 : 1. Brunauer-Emmett-Teller and transmission electron microscopy characterizations showed the obvious mesoporous structure of SnO 2 in PtSnO 2 (M)/C catalyst. X-ray photoelectron spectroscopy analysis exhibited the interaction between Pt and mesoporous SnO 2 . Compared with Pt/C and commercial PtSnO 2 /C catalysts, PtSnO 2 (M)/C ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…Optical microscopy photos of the fabricated sensor array are shown in Figure 3 ) [32]. The decoration with metallic Pt on the surface of the SnO2 thin film is very important for enhancing the gas sensing properties, for example toward hydrogen [33].…”
Section: Resultsmentioning
confidence: 99%
“…Optical microscopy photos of the fabricated sensor array are shown in Figure 3 ) [32]. The decoration with metallic Pt on the surface of the SnO2 thin film is very important for enhancing the gas sensing properties, for example toward hydrogen [33].…”
Section: Resultsmentioning
confidence: 99%
“…Hidayati and co‐workers showed that the electro‐oxidation of ethanol and CO was improved by the modification of Pt with Sn and SnNi; Sn oxides provided oxygenated species at smaller potentials than pure Pt [20] . Moreover, the mesoporous structure of SnO 2 was exhibited to enhance electrocatalytic activity toward EOR [21] . SnO 2 in Pt−Sn electrocatalysts thus plays an important role to enhance the EOR activity.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Moreover, the mesoporous structure of SnO 2 was exhibited to enhance electrocatalytic activity toward EOR. [21] SnO 2 in PtÀ Sn electrocatalysts thus plays an important role to enhance the EOR activity.…”
Section: Introductionmentioning
confidence: 99%